Louis Couturat: the history of modern symbolic logic and other French manuscripts - Schlaudt, Oliver; Schmid, Anne-Françoise (Science autour de / around 1900, 2021)
Introduction -- Acknowledgements -- List of Editorial Symbols -- I Cours de Caen 1898–1899 -- II Cours 1905-1906: Histoire de la Logique formelle moderne -- III Manuel de Logistique. Tome I -- IV Manuel de Logistique. Tome II.